An overview of rapid non-culture-based techniques in various clinical specimens for the laboratory diagnosis of Talaromyces marneffei - Wei, Huamei; Thammasit, Patcharin; Amsri, Artid; Pruksaphon, Kritsada; Deng, Fenglian; Nosanchuk, Joshua D.; Youngchim, Sirida (Frontiers in Cellular and Infection Microbiology, 2025)
Talaromyces marneffei (T. marneffei) is a temperature-dependent biphasic deep opportunistic infectious fungus that primarily affects individuals with advanced HIV disease and other immunocompromised populations. Traditional diagnostic methods rely on fungal culture, but this process, although sensitive, is time-consuming and susceptible to contamination. Therefore, non-culture techniques serve as important complementary and alternative methods for diagnosing talaromycosis. They enable faster and more convenient pathogen identification, improving diagnostic efficiency and facilitating earlier initiation of treatment. Patients with talaromycosis can present with a wide range of clinical symptoms, and different clinical samples require different detection techniques. Blood samples are the most versatile, as laboratory technologists can utilize a wide range of diagnostic methods to obtain accurate results, particularly in the setting of a suspected disseminated infection. In contrast, urine diagnosis relies primarily on immunological methods that detect an antigen abundantly secreted during an infection. Moreover, for invasive samples like bronchoalveolar lavage fluid or cerebrospinal fluid, metagenomic next-generation sequencing is likely to be of significant importance for the early diagnosis due to its high sensitivity and specificity, though this approach is not yet standardized or widely available. For tissue samples, histopathology for light microscopy analysis is a well-established basic method, but it relies on experienced laboratory personnel, is time-consuming, and the histological appearance of other fungi can overlap with T. marneffei. Recent advances in rapid non-culture-based methods diagnostics underscore the growing importance of these tools in clinical settings, particularly for resource-limited areas where culture facilities are inadequate or unavailable. These methods improve diagnostic turnaround time and may lead to better clinical outcomes, especially for vulnerable patient populations. This review emphasizes the need for ongoing development and validation of non-culture diagnostics, with a focus on standardization, accessibility, and integration of rapid molecular and immunological tools to improve early detection and patient management in endemic regions.